Acutely induced cell mortality in the unicellular green alga Chlamydomonas reinhardtii (Chlorophyceae) following exposure to acrylic resin nanoparticles. Issue 1 (26th November 2018) - Widyaningrum, Dwiyantari; Iida, Daisuke; Tanabe, Yuma; Hayashi, Yasuko; Kurniasih, Sari Dewi; Ohama, Takeshi
Abstract : Nanoparticles have unique properties that make them attractive for use in industrial and medical technology industries but can also be harmful to living organisms, making an understanding of their molecular mechanisms of action essential. We examined the effect of three different sized poly(isobutyl‐cyanoacrylate) nanoparticles (iBCA‐NPs) on the unicellular green alga Chlamydomonas reinhardtii . We found that exposure to iBCA‐NPs immediately caused C. reinhardtii to display abnormal swimming behaviors. Furthermore, after one hour, most of the cells had stopped swimming and 10%–30% of cells were stained with trypan blue, suggesting that these cells had severely impaired plasma membranes. Observation of the cyto‐ultrastructure showed that the cell walls had been severely damaged and that many iBCA‐NPs were located in the space between the cell wall and plasma membrane, as well as inside the cytosol in some cases. A comparison of three strains of C. reinhardtii with different cell wall conditions further showed that the cell mortality ratio increased more rapidly in the absence of a cell wall. Interestingly, cell mortality over time was essentially identical regardless of iBCA‐NP size if the total surface area was the same. Furthermore, direct observation of the trails of iBCA‐NPs indicated that the first trigger was their contact with the cell wall, which is most likely accompanied by the inactivation or removal of adsorbed proteins from the cell wall surface. Cell mortality was accompanied by the overproduction of reactive oxygen species, which was detected more readily in cells grown under constant light rather than in the dark.